2002
DOI: 10.1248/bpb.25.256
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic Effect of Flavonoid Glycosides Obtained from Mentha piperita L.

Abstract: Six flavonoid glycosides, eriocitrin (1), narirutin (2), hesperidin (3), luteolin-7-O-rutinoside (4), isorhoifolin (5), diosmin (6), rosmarinic acid (7) and 5,7-dihydroxycromone-7-O-rutinoside (8), were isolated from the aerial part of Mentha piperita L. Among these compounds, compound 4 showed a potent inhibitory effect on histamine release induced by compound 48/80 and antigen-antibody reaction. This compound was more effective than luteolin and luteolin-7-O-glucoside in inhibiting histamine release from rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 10 publications
3
96
0
2
Order By: Relevance
“…To date, many low-molecularweight polyphenols have been reported as anti-allergic substances that inhibited the degranulation process. [30][31][32][33][34][35] Some of these polyphenols are known to suppress classswitching from IgM to IgE in B cells or the expression of Fc"RI and subunits in mast cells. [36][37][38] Quince fruit has been reported to contain low-molecular-weight polyphenols such as caffeoylquinic acids (3-, 4-, and 5-caffeoylquinic acids and 3,5-dicaffeoylquinic acid), quercetin glycosides (quercetin-3-galactoside and quercetin-3-rutinoside), and kaempferol glycosides (kaempferol-3-glucoside and kaempferol-3-rutinoside) in the pulp, peel, and seeds.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many low-molecularweight polyphenols have been reported as anti-allergic substances that inhibited the degranulation process. [30][31][32][33][34][35] Some of these polyphenols are known to suppress classswitching from IgM to IgE in B cells or the expression of Fc"RI and subunits in mast cells. [36][37][38] Quince fruit has been reported to contain low-molecular-weight polyphenols such as caffeoylquinic acids (3-, 4-, and 5-caffeoylquinic acids and 3,5-dicaffeoylquinic acid), quercetin glycosides (quercetin-3-galactoside and quercetin-3-rutinoside), and kaempferol glycosides (kaempferol-3-glucoside and kaempferol-3-rutinoside) in the pulp, peel, and seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The release percentage of histamine was calculated by the following equation. 49,50 Histamine release…”
Section: Mast Cell Sensitization By Compound 48/80 and Microscopic Obmentioning
confidence: 99%
“…Peppermint leaf and oil contain acetaldehyde, amyl alcohol, menthyl esters, limone, pinene, phellandrene, cadinene, pugelone, and dimethyl sulfide. Trace constituents include alpha-pinene, sabinene, terpinolene, ocimene, gammaterpinene, fenchene, alpha-and beta-thujone, citronellol, and other compounds (Nair, 2001;Inoue et al, 2002).…”
Section: Peppermint (Mentha Piperita)mentioning
confidence: 99%
“…Trace constituents include alphapinene, sabinene, terpinolene, ocimene, gamma-terpinene, fenchene, alpha-and beta-thujone, citronellol, and other compounds. Nair B, 2001;Inoue et al, 2002 Allergic reactions and conjunctivitis (Paulsen, 2002;De Smet, 2002) Warfarin Citochrome P450 (Segal and Pilote, 2006) Nettle Osteoarthritis. BPH Allergic rhinitis (hayfever) (Mittman, 1990;Lopatkin et al, 2005) Uterine-stimulant effects, it can induce abortion (Heinrich, 2003;Gagnier et al, 2006) None reported…”
Section: Pepermintmentioning
confidence: 99%